The hyperchromatic supranuclear stria corresponds to the Golgi apparatus in nasal ciliated cells - Gelardi, Matteo; Guerra, Lorenzo; Giangregorio, Nicola; Cassano, Michele; Favia, Maria; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
.